An Analysis of Figurative Language in Eleven Stories by Leo Tolstoy - Selvi Dalmayanti; Arman Arman (ELITE: Journal of English Language and Literature, 2017)
This study aims to find out the types of figurative language and the most dominant types of figurative language that used in short stories God Sees the Truth but Waits, Esarhaddon, King of Assyria, and Too Dear by Leo Tolstoy. The methodology of this study used descriptive qualitative method because the data are in form of words and utterance rather than the number. The source of data in this study is three short stories of Leo Tolstoy that taken from storage.cloversites.com. Some techniques in analyzing the data consist of classifying the data that need to be analyzed described the data and interpreting the data based on Leech’s categories and the last made the conclusion to answer the research question. This study used the theory of figurative language based on Geoffrey Leech’s categories. Based on the findings, there are four types of figurative language that was found in the short stories, they are hyperbole (5 data), metaphor (2 data), Litotes (2 data), and Simile (10 data). The most dominant figurative language used is a simile for 10 data.